Keragaman Tanaman Obat dalam Lontar “Taru Pramana” dan Pemanfaatannya untuk Pengobatan Tradisional Bali - Arsana, I Nyoman (Jurnal Kajian Bali (Journal of Bali Studies); Vol 9 No 1 (2019): WACANA KRITIS BUDAYA BALI, 2019)
“Taru Pramana” lontar manuscripts contain medicinal plant diversity and it uses for traditional system of Balinese medicine. This study aims to describe medicinal plant diversity in “Taru Pramana” lontar manuscripts and its use for traditional system of Balinese medicine. This research uses the library method. The unit of analysis is the “Taru Pramana” lontar manuscript from collection of the Leiden University Library, Netherlands. The data obtained were analyzed descriptively. The ethnosystem approach is used as the main approach in this analysis, which places an emic perspective on the relationship between humans and plants. A total of 182 plant species are used in traditional Balinese medicine, mostly including family members of euphorbiaceae, moraceae, fabaceae, and zingiberaceae. The parts used were leaves, shoots, stem bark, roots, fruit, sap, tuber and used them into various forms of medicine such as loloh, boreh, sembar, tutuh, tempel, and ses. The practice of the use of medicinal plants in traditional Balinese medicine is based on a strong belief and knowledge system.